Analisis Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa STEI SEBI Jurusan Akuntansi Syariah terhadap Profesi Akuntan Publik - Niswatul Mahmudah (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2014)
This study aims to determine the factors that affect SEBI student interest subject toIslamic Accounting Public Accounting profession. These are intrinsic work values ,socio-economic and personality factors. The findings showed that the number of IslamicAccounting students are not interested in the profession of public accounting is fargreater than the number of students interested in the public accounting profession, whichis 22: 60. This research note that, although more than 50% students of Islamic Accounting class of 2008 and 2009 have a grasp of the Public Accounting profession, but thewhole or 100% of these students have never had an internship experience in PublicAccounting Firm (KAP). The study found the three factors of intrinsic work factors,socio-economic and personality are not significantly affect the interest of students towards public accounting profession